Descending projections from the auditory cortex to the inferior colliculus in the gerbil, Meriones unguiculatus. - Bajo, V; Moore, DR (2005)
Corticofugal projections to the auditory midbrain, the inferior colliculus (IC), influence the way in which specific sets of IC neurons process acoustic signals. We used retrograde tracer (Fluorogold, Fluororuby, microbeads) injections in the IC to study the morphology and location of cortico-collicular projecting neurons and anterograde tracer (dextran biotin) injections in auditory cortical fields to describe the distribution of terminals in the IC. Nissl staining, cytochrome oxidase activity, and neurofilament SMI32 immunostaining were used to delimit the different auditory areas. We defined a primary or "core" auditory cortex and a secondary "caudal" auditory area containing layer V pyramidal neurons that project to the IC. These projections target the central nucleus of the IC (CNIC) ipsilaterally and the IC cortices bilaterally, with the ipsilateral component predominant. Other secondary auditory areas, dorsal and ventral to the core, do not directly participate in this projection. The ventral secondary cortex targets midbrain periaqueductal gray. The projection from the core cortex originates from two classes of layer V pyramidal cells. Cells presenting a tufted apical dendrite in layer I have dense terminal fields in the IC cortices. Pyramids lacking layer I dendritic tufts target the CNIC in a less dense but tonotopic manner. The caudal cortex projection originates from smaller layer V pyramids and targets the IC cortices with dense terminal fields. Descending auditory inputs from the core and caudal areas converge in the dorsal and external cortices of the IC. Descending connections to the gerbil IC form a segregated system in which multiple descending channels originating from different neuronal subpopulations may modulate specific aspects of ascending auditory information.